The Church of Georgia in War - TSURTSUMIA, Mamuka (Historia i Świat, 2019)
In Western Europe the Church as an institution was integrated into the military system and was obliged to serve the monarchy. Apart from performing vassal duties, the Latin clergy frequently participated in military actions. Although the Church laws forbade clergymen to shed blood, there were many examples of the violation of this rule. The attitude of the Orthodox Church in the Byzantine Empire concerning the possible participation of the clergy in war differed significantly from that of Latin Europe. The Byzantine priesthood did not become involved in military actions. The Greek Church possessed neither military units nor vassal commitment to the Empire. Despite a very close relationship with the Byzantine Church the attitude of the Georgian Church to the issue differs from that of Byzantium and is closer to the Western practice. The feudal organization of Georgia conditioned the social structure of the Georgian Church and its obligations before the monarchy. Despite the fact that the Georgian Church enjoyed many advantages, it had to take part in military campaigns. The upper circles of Georgian Church dignitaries were accustomed to both conducting military campaigns or taking part in the combat. In regard to military activities of clergy, Georgian law was much more lenient than Byzantine, and in the case of necessity, it even modified Greek legal norms. The conflict with the Christian canons was decided in favor of military necessity, and it was reflected in the legislation.